2020
DOI: 10.1016/j.jjcc.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of population density on mortality in patients hospitalized for heart failure – JROAD-DPC Registry Analysis –

Abstract: Background: There is little evidence regarding social and geographic factors in patients with heart failure (HF). We sought to investigate the association between in-hospital mortality of patients with HF and population density of the patients' area of residence in Japan. Methods: The present study is a retrospective cohort analysis of the nationwide claim-based database, the Japanese Registry Of All cardiac and vascular Diseases-Diagnostic Procedure Combination (JROAD-DPC). We selected data of 196,286 hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Third, the high mortality rate may be due to the inclusion of hospitals not specialized in treating cardiovascular diseases. Evidence has shown that in-hospital mortality rates are lower in hospitals with a large number of subspecialty departments [ 30 ], in hospitals with more cardiologists per cardiovascular bed [ 16 ], and in areas with higher population density [ 17 ]. Furthermore, while there are no studies to date that have investigated differences in the implementation of the AHF guidelines between hospitals in Japan, evidence from other cardiology areas and countries indicates that such differences are likely [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the high mortality rate may be due to the inclusion of hospitals not specialized in treating cardiovascular diseases. Evidence has shown that in-hospital mortality rates are lower in hospitals with a large number of subspecialty departments [ 30 ], in hospitals with more cardiologists per cardiovascular bed [ 16 ], and in areas with higher population density [ 17 ]. Furthermore, while there are no studies to date that have investigated differences in the implementation of the AHF guidelines between hospitals in Japan, evidence from other cardiology areas and countries indicates that such differences are likely [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent Japanese studies, such as registry-based studies [10], electronic medical records [EMR]/claims studies [13][14][15][16][17], and retrospective chart review studies [18], have investigated treatment patterns and/or outcomes during AHF hospitalizations in Japan. Nevertheless, gaps in knowledge remain.…”
Section: Introductionmentioning
confidence: 99%
“…Since a similar trend also was apparent in 2019, a fixed regional effect caused by unknown structural differences is likely to influence the results. For example, population density has been shown to impact in‐hospital outcomes in HF patients 17 . An uneven distribution of cases discharged as hospital transfers between different areas could also contribute to this finding, as those cases were excluded from our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, population density has been shown to impact in-hospital outcomes in HF patients. 17 An uneven distribution of cases discharged as hospital transfers between different areas could also contribute to this finding, as those cases were excluded from our analysis. This was done to avoid a biased in-hospital death rate because no crosslinking of patient cases between hospitals was possible due to data structure and data privacy.…”
Section: Discussionmentioning
confidence: 99%
“…17) Because comorbidities, disabilities, and frailty are more com- mon in elderly patients with HF, 18,19) elderly outpatients with HF presenting NYHA functional class !III tended to be followed by general practitioners rather than by cardiologists in Europe. 20,21) Similar to Europe, a Japanese nationwide questionnaire survey suggested cardiologists answered that the barriers to follow-up with cardiologists include the difficulty for HF patients to visit outpatient cardiology clinics because most HF patients are elderly and frail or have no caregivers. 22) The statement of the JCS suggested that comprehensive medical care by general physicians has become more critical as the severity of heart failure has progressed and the care by general physicians should be increasing for patients with more advanced HF stage.…”
Section: Discussionmentioning
confidence: 99%